The Theological Programme of Mark: Exegesis and Function of Mark 1:1,2–15 - Filannino, Francesco (Wissenschaftliche Untersuchungen zum Neuen Testament 2. Reihe, 2021)
"The first chapters of literary works are indispensable to understanding them. This is also true of the Gospels. Francesco Filannino shows that the introductory section of Mark's Gospel (Mark 1:1-15) is an important key to accessing the whole narrative, because it anticipates the main contents of the evangelist's theology."